Customer attitude towards credit card practices study case in Kota Bharu Kelantan / Nadiah Abdul Aziz - Abdul Aziz, Nadiah (2012)
This research is conducted to study the customer attitude toward credit card practices in Kota Bharu. The objectives of this research are to identify the credit card practices and to determine significant relationship between the monthly income, personal financial practices and attitude with credit card pactices. Moreover, this study is to determine whether the three independent variables that have been taken as measurements that are monthly income, personal financial knowledge and attitude being influenced or not towards the dependent variable that is credit card practices in Kota Bharu. The study done by using the primary data as sources .The results show that there is some positive relationship between the measurements taken with the credit card practices in Kota Bharu. From the result that I have gained, it stated that, attitude have significant relationship with dependent variable, credit card practices. Besides, monthly income and personal financial knowledge has no significant relationship with credit card practices in Kota Bharu.